Design Guidelines of Public Toilet by using Participatory Design A Case Study of Public Toilet Wat Phra That Cho Hae, Phrae Province. - Tammikakul, Phichayapa (RMUTL Journal of Socially Engaged Scholarship, 2023)
This research is the study of public toilet improvement guidelines. A case study of public toilets Wat Phra That Cho Hae, Phrae Province by adopting a user-centered design process and participatory design. To be applied in order to design and improve the bathroom inside Wat Phra That Cho Hae. Support for all people in the community and help design an environment that promotes the well-being of the community. The research process was as follows: 1) physical survey of the toilet at Wat Phra That Cho Hae at present 2) Action activities, brainstorming ideas in accordance with the needs of users in the community and the context 3) Presenting a draft for decision making. Determine the desired style. 4) Renovate and develop the design of the bathroom improvements in Wat Phra That Cho Hae. 5) Present and summarize the design results to deliver to the community. The results of the research concluded that The last model is chosen from the advantages of and the possibility of a final draft to be developed and delivered to the Wat Phra That Cho Hae community. To be used to renovate old, deteriorated bathrooms to be clean and hygienic. as well as mentioning the surrounding context is important In addition to considering the materials used and the budget is important as well.